Limited Attention Diminishes Spatial Suppression From Large Field Glass Patterns. (April 2019) - Pavan, Andrea; Contillo, Adriano; Ghin, Filippo; Foxwell, Matthew J.; Mather, George
Glass patterns (GPs) consist of randomly distributed dot pairs (dipoles) whose orientations are determined by specific geometric transforms. We investigated the role of visuospatial attention in the processing of global form from GPs by measuring the effect of distraction on adaptation to GPs. In the nondistracted condition, observers were adapted to coherent GPs. After the adaptation period, they were presented with a test GP divided in two halves along the vertical and were required to judge which side of the test GP was more coherent. In the attention-distracted condition, a high-load rapid serial visual presentation task was performed during the adapting period. The magnitude of the form after-effect was measured using a technique that measures the coherence level at which the test GP appears random. The rationale was that if attention has a modulatory effect on the spatial summation of dipoles, in the attention-distracted condition, we should expect a weaker form after-effect. However, the results showed stronger form after-effect in the attention-distracted condition than in the nondistracted condition, suggesting that distraction during adaptation increases the strength of form adaptation. Additional experiments suggested that distraction may reduce the spatial suppression from large-scale textures, strengthening the spatial summation of local-oriented signals.